2019
DOI: 10.1186/s12917-019-2092-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and pathogenicity of fowl adenovirus serotype 4 isolated from eastern China

Abstract: BackgroundFowl adenovirus outbreaks have occurred in China since June 2015. This virus is an emerging infectious disease that causes hydropericardium syndrome and inclusion body hepatitis (HPS-IBH), resulting in significant economic loss to poultry farmers. Five fowl adenovirus (FAdV) strains (HN, AQ, AH726, JS07 and AH712) were isolated from Jiangsu and Anhui provinces.ResultsPhylogenetic analysis revealed that the five isolates belonged to species C fowl adenovirus serotype 4. An 11 amino-acid deletion in OR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
0
22
0
1
Order By: Relevance
“…IL-1β and IL-2 play a role in the activation and regulation of the immune system depending on the pathophysiological condition ( Wang et al., 2014 ). IFN-γ is critical for host defense against a variety of pathogens ( Wang et al., 2019 ). In the present study, we showed that GCP increased the expression of IL-1β, IL-2, and IFN-γ at both day 21 and 42.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β and IL-2 play a role in the activation and regulation of the immune system depending on the pathophysiological condition ( Wang et al., 2014 ). IFN-γ is critical for host defense against a variety of pathogens ( Wang et al., 2019 ). In the present study, we showed that GCP increased the expression of IL-1β, IL-2, and IFN-γ at both day 21 and 42.…”
Section: Discussionmentioning
confidence: 99%
“…The chicken liver hepatocellular carcinoma cell line LMH was purchased from the American Type Culture Collection (ATCC); LMH cells were cultured in DMEM/F12 (Gibco, NY, United States) supplemented with 10% fetal bovine serum (FBS) (Gibco). The FAdV-4 strain HN and FAdV-8a strain AH720 were isolated as described previously ( Wang et al, 2019 ; Lv et al, 2021 ) and allowed to replicate in LMH cells. SPF chickens were purchased from Merial Vital Laboratory Animal Technologies Co., Ltd. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, the FAdV-4 strain HN and FAdV-8a strain AH720, isolated from chickens from poultry farms in Hunan and Anhui provinces, respectively, were identified and characterized ( Wang et al, 2019 ; Lv et al, 2021 ). In the present study, we aim to establish a chicken model of co-infection with both these stains to investigate the interactions between FAdV-4 and FAdV-8a in specific-pathogen-free (SPF) chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by ( Niu et al, 2018 ) indicated that polyclonal antibodies, based on hexon regions loops L1 and L2, could be used as a detection of antibody in IHC analysis to elucidate the distribution of the virus in target organs, especially the liver ( Niu et al., 2018 ). Wang, 2019 indicated that phylogenetic analysis of five adenovirus strains belonged to type/species 4/C and indicated an 11 amino-acid deletion in ORF29 which was related to older viral strains and during in vivo studies on chickens indicated lesions characteristic for HP-IBH.…”
Section: Discussionmentioning
confidence: 99%